Trainer complex for special strength training of swimmers on the surface and in water - Panarin, B. (1998)
The aim of the investigation is to elaborate the trainer complexes which would help to develop specific strength qualities of swimmers. The trainer apparatus (patent N 1614819 A 63B 69/10) consists of: frame fastened to the board of the swimming-pool vertically where carriages with shovels are located and can be rotated around the axis. The carriages are tied by the ropes with handles. The swimmer is on the board of the swimming-pool and grips the handles; he performs a rowing movement as if he were swimming. The shovels are in water in the low initial position and are turned and fixed in rest in a horizontal plane during the period of the rowing movement; they move up, creating resistance to the movement. In the upper position the carriages engage with shock-absorbers which accelerate the return of the carriage to the low initial position after finishing the rowing movement. The shovels turn the spin at that moment, fold up and create resistance to the downward carriage movement. The construction (patent N 1273130 A63B 69/12) includes a belt for the swimmer linked with a hindrance device attached to a directing rope, fastened above the water surface on the boards of the swimming-pool. The swimmer, moving from one board to another in the water, overcomes the given resistance of the hindrance device which moves after it. The power of the work done is determined according to the formula: N=L*P/t, where: L= length of the distance, P= value of the resistance, t= time. The construction (patent N 1621983 A63B 69/12), the prototype of which is the device "Swim-On" (USA), includes: handles for the hands linked by non-elastic cords to the swimming-pool boards, a loading device for different kinds of loads which is located on the post on the opposite board of the swimming-pool and linked by means of blocks and a cable with the belt of the swimmer. The swimmer is in the water in a stretching initial position, leaning on the handles during his performance, the rowing movement moves forward, overcoming the resistance of lifting the load. After finishing the rowing movement, the load lowers, creating the strength of the traction which is put on the belt, and as a result the swimmer returns to the initial position. The power of the work done is determined according to the formula: N=P*h*n, where: P= weight of the load, h= height of the lifting of the load, n= tempo of the movements. The constructions are being applied in the training process of the Lviv Physical Culture Institute and region team. The parametres of the loading: the size of the resistence (loading), the length of the distance, the time are given with the account of the fulfillment of the work at a certain level of power in accordance with the planned sports results.